CHANGING TEACHERS’ ROLE IN PRIMARY SCHOOL (TAMADDUN NURI JURNALI, 2024)
This article discusses the role of teachers in primary school and its importance and difficulties on pupils’ imparting, changing their life. How to perfectly organize the lessons according to the learner’s age and degree of knowledge properly. The ways and new methods which are very essential to make learners be independent, easy-going and specially inquisitive will be analyzed.